2015
DOI: 10.1007/s10528-015-9696-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Effect of CYP2C8*3 on the Risk of Essential Hypertension in Bulgarian Patients

Abstract: We conducted a case-control study to determine the contribution of polymorphisms in CYP2C8 (CYP2C8*3) and CYP2J2 (CYP2J2*7) to increased risk of coronary artery disease and essential hypertension in Bulgarians. The current analysis included 192 unrelated hypertensive patients, 261 patients with angiographically documented CAD (153 with myocardial infarction and 108 without myocardial infarction), and 496 population controls. The CYP2C8*3 and CYP2J2*7 polymorphisms were genotyped by TaqMan SNP Genotyping Assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…CYP2C8 gene polymorphisms were found to be associated with essential hypertension (EH) ( 21 ). CYP2C8 *3 allele was statistically significantly more frequent in men with EH ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C8 gene polymorphisms were found to be associated with essential hypertension (EH) ( 21 ). CYP2C8 *3 allele was statistically significantly more frequent in men with EH ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study performed by Fava and colleagues [20] investigated the relationship among the rs890293 poly morphism, blood pressure and hypertension risk in a large urban-based sample of Swedes with hypertension (N = 1858). The results from these studies have been conflicting: two studies performed in Russian [31] and Saudi Arabian [32] populations indicated a strong positive association between SNP rs890293 and hypertension risk; in contrast, one study in white Americans showed a negative associa tion of this polymorphism and disease risk [28], whereas studies conducted in Swedish [20], Bulgarian [33] and African American [29] populations did not identify a rela tionship between the SNP and hypertension susceptibility.…”
Section: Polymorphisms Of Cyp2j2 and Their Relationship With Hypertenmentioning
confidence: 99%
“…To date, only seven studies have been conducted to assess associations between polymorphisms of the CYP2J2 gene and hypertension susceptibility: four studies in Caucasians [20,28,31,33], two studies in Asians [30,32] and one study in blacks [29]. Five of these studies investigated the association of hypertension with the only one SNP rs890293 (-5 0 or -76G>T) located at the promoter of CYP2J2 in small population samples (<200 EH patients).…”
Section: Polymorphisms Of Cyp2j2 and Their Relationship With Hypertenmentioning
confidence: 99%
See 1 more Smart Citation
“…Human CYP2C8 and CYP2C9, thought to be the primary CYP2C epoxygenases, are both abundantly expressed in kidney and have a similar function (Enayetallah et al, 2004). Studies with the human single nucleotide polymorphism CYP2C8*3 have shown either a small but significant association with hypertension (Tzveova et al, 2015) or no association with hypertension (Dreisbach et al, 2005;King et al, 2005). Further studies will be needed to clarify the association between polymorphisms such as CYP2C8*3 and hypertension in humans.…”
mentioning
confidence: 99%